PEMBUATAN TES KECERDASAN SISWA BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract- IQ tests on SMA Sultan Agung Semarang for this is still done in a way that is manually done by providing the questions on a piece of paper that is capable of measuring a person's IQ with output in the form of numerical data. To determine the IQ test results still need to wait at least a few days. The hope this test will result as a reference for determining majoring in science or social studies of high school students Sultan Agung Semarang. System development method used in this study is a waterfall that consists of beginning the system, system analysis, system design, system implementation and system testing. System design using UML which consists of a use case diagrams, state diagrams, sequence diagrams and class diagrams. Making programs using PHP and MySQL. The end result of this research is the application of IQ tests at SMA Sultan Agung Semarang web-based to facilitate SMA Sultan Agung Semarang to administer tests to assess IQ and IQ test results can be used to perform majors IPA or IPS Keywords – IQ Test, UML, IPA, IPS